Adjustment experiences of adolescents living with well-controlled type 1 diabetes using closed-loop technology - Kruger, Sylvia; Deacon, Elmari; van Rensburg, Esmé; Segal, David (Frontiers in Clinical Diabetes and Healthcare, 2024)
AimThis study aimed to obtain an in-depth understanding of the experiences of adolescents with well-controlled type 1 diabetes who were adjusting to closed-loop technology.MethodInterpretative Phenomenological Analysis (IPA) was conducted. Five participants (aged 15–18) were recruited from the Centre for Diabetes and Endocrinology in Parktown, South Africa, to participate in semi-structured interviews about their experiences of adjusting to closed-loop technology.ResultsFive superordinate themes emerged (1): learning to trust the technology (2), making diabetes visible (3), building a relationship with diabetes (4), empowering support networks, and (5) transformative positive outcomes. The findings demonstrate that closed-loop technology positively impacts the adjustment to living with type 1 diabetes. However, as highlighted by all participants, the individual’s engagement and management are crucial. Based on the adolescents’ experiences, interventions should focus on psychological factors.